MORPHOLOGY AND MORPHOMETRIC STUDY OF MANDIBLE OF ASIATIC LION (Panthera leo), INDIAN TIGER (Panthera tigris) AND COMMON LEOPARD (Panthera pardus) - Pandya, Sweta; Bhayani, DM; Yyas, YL (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The morphology and morphometric study on mandibles of lion, tiger and leopard was carried out at Sakkarbaug Zoo, Junagadh (Gujarat). The mandible is formed by two symmetrical halves fused rostrally by symphysis. The alveolar border presented six alveoli for lower incisors and two large deep alveoli for canine teeth. The average length of mandible was 19.08, 17.40 and 13.54 cm in lion, tiger and leopard, with the corresponding average mandible weight of 0.338, 0.271, and 0.145 kg, respectively. However, the width of mandible was significantly more in lion (3.28 cm) than that of tiger (2.51 cm) and leopard (1.71 cm). The mandibular height up to condyle and coronoid process in lion, tiger and leopard was 4.17 and 9.24, 4.19 and 9.16, 3.04 and 7.14 cm, respectively. Both the heights were significantly higher in lion and tiger than those of leopard. The average length of symphysis-mandibularis was significantly higher in lion (6.58 cm) and tiger (6.68 cm) than leopard (4.47 cm). The mental foramina were three in tiger and two in lion and leopard, and they were deeper in lion and tiger than the leopard. The angular process was placed at caudal border of horizontal ramus and found blunt and medially curved in all three species.